Effect of nitrogen doping on the thermal conductivity of GeTe thin films. Issue 12 (6th September 2013) - Fallica, Roberto; Varesi, Enrico; Fumagalli, Luca; Spadoni, Simona; Longo, Massimo; Wiemer, Claudia
Abstract The 3ω method was employed to determine the effect of nitrogen doping (5 at.%) on the thermal conductivity of sputtered thin films of stoichiometric GeTe (a material of interest for phase change memories). It was found that nitrogen doping has a detrimental effect on the thermal conductivity of GeTe in both phases, but less markedly in the amorphous (–25%) than in the crystalline one (–40%). On the opposite, no effect could be detected on the measured thermal boundary resistance between these films and SiO2, within the experimental error. Our results agree with those obtained by molecular dynamic simulation of amorphous GeTe. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)